PEMBINAAN DAN PELATIHAN KADER PENGURUS DANPENGELOLA BARUPENDIDIKAN ANAK USIA DINI (PAUD)CERDAS DUSUN BANDUNGDAN DUSUN SONGBANYU 1, KECAMATAN SONGBANYU, GUNUNG KIDUL,DAERAH ISTIMEWAYOGYAKARTA - Muntoha Muntoha (UII, 2015)
Pendidikan Anak Usia Dini (PAUD) is a development effort that is intended forchildren from birth up to the age of six years are accomplished by providing educationalstimuli to help the growth and developmentof children physically and mentally in orderto have the readiness to enter further education. The concept of the benefits of PAUD isnone other empowered so that kids are getting ready when entering primary education.Unfortunately, with the benefit of it, PAUD often underestimated and many not so careabout. As happens in PAUD Cerdas Dusun Bandung dan Dusun Songbanyu 1. That PAUDuntil now are still being taught by someone who has years of being a teacher. There is nonew teachers in that PAUD. Therefore, author does initiate regeneration for PAUDrejuvenation. Teachers were younger will inject moral and greater enthusiasm in thefuture.